THREE-YEAR COMPARATIVE ANALYSIS OF THE PRESENCE OF MENINGIOMAS AND SECONDARY DEPOSITS IN THE BRAIN - Nikolov, Vesna (Acta medicae Medianae, 2022)
About 16% of the world’s population is covered by registration systems that provide cancer incidence statistics, while mortality data are available for about 29%. The percentage of metastatic changes in the brain, as secondary deposits, is also increasing. Meningiomas are most often slow-growing, benign, primary intracranial tumors in adults, middle-aged (45 to 55 years). Early detection, favorable localization in the brain and well-performed surgery bring good results to the patient in terms of improved outcome. A retrospective study included patients with metastatic changes in the brain and meningiomas treated at the Clinic of Neurosurgery and the Clinic of Oncology of the University Clinical Center Niš in the period from the beginning of 2018 to the end of 2020. By comparing the ratio of the presence of meningioma, as benign tumors in the brain, in relation to the percentage of secondary deposits present, we come to the conclusion that malignancy is on the rise. Early diagnosis and suspicion of this dissemination in primary metastasis enable surgical intervention followed by oncological treatment, which together prolong the patient’s life. Comparing the patients with meningioma who underwent surgery in the period from 2018 to 2020 according to gender, age structure, tumor localization, no statistically significant difference was observed. Females are ahead of males in terms of meningioma. There has been an evident increase in malignancy in recent years in both genders. In meningioma, the treatment is surgical. In case of solitary changes after surgery, oncological treatment is performed. In the case of multiple changes in the brain, the treatment is oncological, which includes the use of radio and chemotherapy.